Effects of Irisin on Reproductive Parameters in High Fat Diet Induced Obese Male Rats - Yardimci, Ahmet; Ulker, Nazife; Gungor, Ibrahim Halil; Bulmus, Ozgur; Canpolat, Sinan (Karger, 2021)
[Abstract Not Available]
Keywords: Obesity; irisin; accessory sex organ; sperm parameter